FeCl3-Catalyzed Cascade Reactions for Construction of Cyclopentane-Fused Cyclized Spirobicyclized-Indole and Bis(indolyl)methane Scaffolds - Kumar, Ravan; Das, Arka; Khatun, Saheba; Banerjee, Amit; Gupta, Sreya; Saha, Sumit (Synthesis, 2025)
Ferric chloride (FeCl3) catalyzed synthesis of complex scaffolds of cyclopentane-fused cyclized and spirobi[cyclopenta[b]indole] and bis(indolyl)methanes (BIMs) was achieved from acetone and indoles via cascade reactions. Additionally, the formation of tetrahydro-3H-carbazole was observed from 2-methyl-indole. The reaction proceeded through condensation, addition, and intramolecular cyclization reactions. This protocol explored the target-oriented synthesis of three products from the same substrates by varying reaction conditions. This protocol strikingly features sustainable catalysis using mild and earth-abundant metals as catalysts, readily available substrates, and short reaction times, affording a variety of complex indole scaffolds with moderate to good yields. The synthesized products resemble natural and synthetic biologically active compounds containing cyclopenta[b]indole cores, highlighting their biological importance.
Keywords: Indole; Bisindoles; Cascade reactions; Spiro[bicyclopentane]; Cyclopentane; Cyclization